Raspberry Pi based advanced scheduled home automation system through E-mail - Narender, M.; Vijayalakshmi, M. (2014 IEEE International Conference on Computational Intelligence and Computing Research, 2014)
The process of automation is becoming popular because of its numerous applications. Home automation is something that deals with the control of domestic appliances with the help of local networking or by remote control. The main aim of this paper is to develop an advanced method of home automation with the application of Raspberry Pi (RPi) through reading the subject of the E-mail. An algorithm for the same has been developed using the python environment which is by default provided by Raspberry Pi. The automation process that is employed is a scheduled automation, which is done. The results show an efficiency of the algorithm employed to perform a scheduled automated. These instructions give you basic guidelines for preparing papers for conference proceedings.